THE EXISTENCE OF GREEN SUKUK AS A SUSTAINABLE ISLAMIC FINANCIAL INVESTMENT INSTRUMENT - Khabib Musthofa; Elman Nafidzi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
AbstractThe purpose of this research is to see the role and urgency of green sukuk, in supporting sustainable Islamic finance. The heat of the issue of climate change and concern for environmental sustainability is currently a very serious conversation. The presence of green sukuk in addition to innovation in the investment sector in Islamic finance is also a form of support for sustainable development. This research applies a qualitative method with a literature study approach coupled with analysis, this research can be concluded that green sukuk has the potential to be further developed in Indonesia and green sukuk has a major role in realizing resilience to climate change as seen from the development of green projects such as drought management, flood mitigation, and food security.Keywords: Green Sukuk, Islamic Finance, Sustainability